"They’re My Family Now": The Creation of Community among RVers - Counts, Dorothy Ayers; Counts, David R. (Anthropologica, 2022)
This paper examines living in a recreational vehicle as an alternative lifestyle for retired people in North America. Based on field work in trailer parks and on "boondocking" sites on government land, the paper argues that RVers experience a greater sense of community and fewer of the emotional problems common in old age than those who have chosen other forms of retirement living. It is further argued that the reciprocity which anthropologists have often noted as a key factor in creating social bonds is more easily achieved among RVers than in other settings in North America.